Regional Original Revenue, Regional Expenditure, Economic Growth and Human Development Index (City/Regency Government in North Sumatra Province) - Oktarini Khamilah Siregar (Mahesa Research Center, 2022)
The Human Development Index is an indicator of the success of local governments in improving the welfare of their people. The HDI in the city/district government of North Sumatra Province is only the Medan City government which has a very high category of 80 percent based on the UNDP assessment. The study wanted to test Regional Original Income, Regional Expenditures and Economic Growth the effect on HDI in City and Regency Governments in North Sumatra using a research method with a causal associative approach. The research sample uses panel data from 32 City and Regency Governments during 2019 to 2020. The results show that Regional Original Income and Economic Growth have not been able to increase HDI, while Regional Expenditures can increase HDI in City and Regency Governments in North Sumatra. However, regional spending has not been fully utilized properly in increasing the HDI. It is necessary to increase regional original income by opening up investment in the region and by stimulating regional original income and increasing economic growth so that the quality of human resources increases.